Perencanaan Pemeliharaan Mesin Pompa Centrifugal dengan Menggunakan Metode Reliability Centered Maintenance (RCM): Studi Kasus PT Nabati Asahan - Sinaga, Septri Asri Enjelina; Sembiring, Anita Christine (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2025)
PT Multimas Nabati Asahan is one of the vegetable oil producers that experiences a high frequency of sudden breakdowns in centrifugal pump machines, averaging 12 hours per month, which negatively impacts production target achievement, operational efficiency, and increased production costs. The research methodology includes the identification of critical components, failure analysis through Failure Mode and Effect Analysis (FMEA) and Logic Tree Analysis (LTA) to determine the priority of maintenance actions. The research results show that the mechanical seal is the component with the highest RPN value of 504, followed by the rubber coupling and bearing. From the task selection results, maintenance action recommendations berupa time directed maintenance, condition based maintenance, and failure finding were obtained. The implementation of RCM is capable of reducing the frequency of sudden failures, optimizing maintenance costs, and improving the reliability and productivity of centrifugal pump machines. This research is expected to serve as a strategic reference in the machinery maintenance management system in the palm oil processing industry. Keywords: Reliability Centered Maintenance, FMEA, Logic Tree Analysis, Downtime, Centrifugal Pump Machine.